Електрохемілюмінесцентний принцип сенсорики ендотоксинів - Музика, К. М.; Білаш, О. М.; Рожицький, М. М. (ХНУРЭ, 2010)
For the first time the possibility of electrochemiluminescent (ECL) phenomena using for the development of the sensor on the endotoxine bilirubin determining in aqueous solution were presented. The excitation modes of the ECL phenomena in test solutions with bilirubin, the impact on the analytical signal of pH and concentration of the toxin were studied. The coreactant nature of the bilirubin involvement in the homogeneous ECL-reactions with electrogenerated ion radicals trisbipiridil ruthenium ({Ru(bpy)3}+3) was shown. The proportional ECL emission intensity dependence from bilirubin concentration was demonstrated. Cyclic voltammograms in the positive part of the potentials and the corresponding ECL emission of the analytical system without and in presents of bilirubin were obtained in the sensor with modified diamond-like glassy carbon electrode. Як типовий представник ендотоксинів у роботі був вивчений білірубін, який є продуктом метаболізму еритроцитів. Білірубін є аполярною ліпофільною речовиною. Його нейротоксичність проявляється, зокрема, смертоносною ядерною жовтянкою, що супроводжується подальшим мозковим ущербом у новонароджених.
Keywords: білірубін; ендотоксини; електрохімічна активність; скловуглецевий електрод; ЕХЛ-реакція; біпіридильний комплекс рутенію